The mechanism of selection of innovative solutions tailored to assess the effectiveness of reserves - S. V. Zakharov (Путеводитель предпринимателя)
Effective and correct selection of innovative solutions is the most important part of the entire process of innovation in small businesses. In this regard, the study of the mechanism of selection of innovative solutions based on an assessment of efficiency reserves is an urgent task. In this article by using analytical methods, systems approach, logical methods of study are analyzed and discussed various aspects of the selection process for innovative solutions. It is concluded that the characteristics of the influence of selected factors on the decision and identify efficiency reserves should use the point-factor method with weighted importance.